The Pathological Features of Common Hereditary Mitochondrial Dynamics Neuropathy - Wu, Rui; Lv, He; Wang, Hui; Wang, Zhaoxia; Yuan, Yun (Frontiers in Neuroscience, 2021)
Objectives: Mitofusin 2 and ganglioside-induced differentiation-associated protein 1 are two main mitochondrial dynamics-related proteins. Dysfunction of these two proteins leads to different subtypes of Charcot-Marie-Tooth disease type 2A (CMT2A) and CMT2K. This study aims to report the pathological difference between CMT2A and CMT2K in a large cohort. Methods: Thirty patients with molecularly confirmed CMT2A and nine with CMT2K were identified by next-generation sequencing. Sural nerve biopsies were performed in 29 patients. Results: The patients with both diseases showed length-dependent neuropathy with distal weakness, sensory loss and no deep tendon reflex. Optic neuropathy appeared in 3/30(10%) patients with CMT2A. Tendon contracture appeared in 4/9 (50.0%) patients of CMT2K. Sural biopsy revealed the loss of both myelinated and unmyelinated nerve fibers. Closely packed, irregularly oriented neurofilaments were observed in axons of unmyelinated nerve fibers in both diseases. Another important finding was the ubiquitous presence of smaller, rounded, and fragmented mitochondria in CMT2A and elongated mitochondria in CMT2K in the myelinated and unmyelinated axons. Conclusion: This study confirmed large diversity in phenotypes between CMT2A and CMT2K. Mitochondrial dynamic related variantions can induce different mitochondrial morphological changes and neurofilaments accumulation in axons.